2012
DOI: 10.4314/ajpsy.v15i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders in a prison population in Durban, South Africa

Abstract: Objective: The aim of this study was to determine the prevalence of serious mental disorders in a prison population in Durban, South Africa, one of the largest prisons in the Southern hemisphere. Method: 193 prisoners were interviewed using the Mini Neuro-psychiatric Interview, a screening questionnaire and a demographic questionnaire. Results: The study demonstrated that 55.4% of prisoners had an Axis 1 disorder. The commonest disorder being substance and alcohol use disorders ( 42.0%). 23.3% of prisoners wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
76
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 10 publications
12
76
8
1
Order By: Relevance
“…A study conducted in South Africa reported findings in support of this study as substance use disorder and depression with anxiety disorder were found in 42.0% and 23.3% of the subjects respectively [28]. Other studies carried out in Nigeria and France reported lower proportions of subjects with substance use disorder, depression and anxiety [8,31].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A study conducted in South Africa reported findings in support of this study as substance use disorder and depression with anxiety disorder were found in 42.0% and 23.3% of the subjects respectively [28]. Other studies carried out in Nigeria and France reported lower proportions of subjects with substance use disorder, depression and anxiety [8,31].…”
Section: Discussionsupporting
confidence: 68%
“…The finding is in conformity with findings of a study in Nigeria where majority (83.7%) of the studied subjects had definite diagnosis of psychiatric disorders on CIDI. Studies from Australia, Iran and other parts of the world also found psychiatric morbidity in 80%, 57%, 55.4%, 51.4% and 43% of the studied subjects respectively using standardised instruments [8,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, researchers found that over one-third of prisoners sampled had a mental disorder (Agbahowe et al, 1998).A study of 193 prisoners in Durban South Africa demonstrated that 23.3% of prisoners were diagnosed with current psychotic, bipolar, depressive and anxiety disorders. The majority of prisoners diagnosed as having an Axis 1 disorder (major mental disorders, learning disorders and substance use disorders) in this study were neither diagnosed nor treated in prison (Naidoo and Mkize, 2012).…”
Section: Prison Populationsmentioning
confidence: 99%
“…International figures vary widely from 2% to 94% (e.g. Assadi et al, 2006;Bland, Newman, & Thompson, 1998;Davidson et al, 1995;Goyal et al, 2011;Naidoo & Mkize, 2012;Gunn, Maden, & Swinton, 1991;Teplin, 1990; for review see Andersen, 2004) often depending on the research methodology, the definition of mental illness (Toch, 2007), the disorders that were included and the setting (Andersen, 2004). Yet, available figures on MIO in European prisons is described as 'alarmingly' scarce (Dressing, Kief, & Salize, 2009).…”
Section: Introductionmentioning
confidence: 99%